2016
DOI: 10.1080/15504263.2016.1145779
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training and Work Therapy for the Treatment of Verbal Learning and Memory Deficits in Veterans With Alcohol Use Disorders

Abstract: Objective This study focused on the efficacy of cognitive training for verbal learning and memory deficits in a population of older Veterans with alcohol use disorders. Methods Veterans with alcohol use disorders, who were in outpatient treatment at VA facilities and in early phase recovery (N = 31), were randomized to receive a 3-month trial of daily cognitive training plus work therapy (n = 15) or work therapy alone (n = 16), along with treatment as usual. Participants completed assessments at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 12 publications
2
49
0
Order By: Relevance
“…These findings echo both earlier and more recent controlled studies of memory recovery with short-term or sustained sobriety showing a range of recovery, from little to extensive, after short-term (e.g., 1 week) to long-term (e.g., 1 year or more) sustained abstinence from alcohol (e.g., Bartels et al, 2007;Bates, Voelbel, Buckman, Labouvie, & Barry, 2005;Bell, Vissicchio, & Weinstein, 2016;Butters & Cermak, 1980;Fabian & Parsons, 1983; 852 E.V. Sullivan Leber, Jenkins, & Parsons, 1981;Mann, Gunther, Stetter, & Ackermann, 1999;Pitel et al, 2009;Rosenbloom et al, 2004;Rourke & Grant, 1999;Yohman, Parsons, & Leber, 1985) (for reviews, see Oscar-Berman et al, 2014;Pitel, Eustache, & Beaunieux, 2014).…”
Section: Recovery Of Component Processes Of Memory Functions With Alcsupporting
confidence: 89%
“…These findings echo both earlier and more recent controlled studies of memory recovery with short-term or sustained sobriety showing a range of recovery, from little to extensive, after short-term (e.g., 1 week) to long-term (e.g., 1 year or more) sustained abstinence from alcohol (e.g., Bartels et al, 2007;Bates, Voelbel, Buckman, Labouvie, & Barry, 2005;Bell, Vissicchio, & Weinstein, 2016;Butters & Cermak, 1980;Fabian & Parsons, 1983; 852 E.V. Sullivan Leber, Jenkins, & Parsons, 1981;Mann, Gunther, Stetter, & Ackermann, 1999;Pitel et al, 2009;Rosenbloom et al, 2004;Rourke & Grant, 1999;Yohman, Parsons, & Leber, 1985) (for reviews, see Oscar-Berman et al, 2014;Pitel, Eustache, & Beaunieux, 2014).…”
Section: Recovery Of Component Processes Of Memory Functions With Alcsupporting
confidence: 89%
“…Furthermore, cognitive training was also related to behavioural changes as a trend was found between working memory training and the reduction of drinks per drinking occasion (from 7.07 drinks to 5.58 drinks in the intervention group v. 5.58 drinks to (Khemiri et al, 2019). Verbal learning and verbal memory: One study assessed the effect of a computerised training tool (Posit Science software®) for the enhancement of verbal learning and memory (Bell, Vissicchio, & Weinstein, 2016). The tool is designed to improve several cognitive functions including attention, memory and sensory processing through visual and auditory tasks that progress from elementary to more complex and demanding games.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
“…For example, a recent study showed that CET improved the rate of substance abuse in patients with schizophrenia (Eack et al , ). It has also been shown to be effective in improving cognition for veterans with alcohol‐use disorder (Bell et al ). This improvement may be related to an increase in activation in prefrontal, limbic and striatal regions that was observed in schizophrenia clients with comorbid alcohol‐ or cannabis‐use disorder that underwent a program of CET (Wojtalik et al ).…”
Section: Cognitive Enhancing Agents May Facilitate Behavioral Therapymentioning
confidence: 99%